2017
DOI: 10.1177/0040517517697644
|View full text |Cite
|
Sign up to set email alerts
|

Toward the cottonization of hemp fibers by steam explosion – Part 1: defibration and morphological characterization

Abstract: Fine hemp fibers (cottonized hemp) were processed using steam explosion. The quantification of the defibration rate was performed by image processing. Based on this method, the hemp defibration was optimized using a response surface methodology based on three-variable central composite design for the production of elementary fibers with low variability. Optimal parameters for the steam processes were as follows: time = 4.1 min; temperature = 191℃. Biomass was impregnated with a solution of NaOH (8%) before tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 29 publications
1
24
2
Order By: Relevance
“…As described in a previous publication (Sauvageon et al, 2018) steam explosion appeared to be an efficient process for the cottonization of hemp. It can be seen from Figure 3 Unexpectedly, in this work we demonstrated that in contrast to bleaching (removal of lignin) which did not significantly modify the thermal decomposition of the fibers, the cottonization process greatly increased the thermal stability of the resulting material (+25-30 °C).…”
Section: -Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…As described in a previous publication (Sauvageon et al, 2018) steam explosion appeared to be an efficient process for the cottonization of hemp. It can be seen from Figure 3 Unexpectedly, in this work we demonstrated that in contrast to bleaching (removal of lignin) which did not significantly modify the thermal decomposition of the fibers, the cottonization process greatly increased the thermal stability of the resulting material (+25-30 °C).…”
Section: -Discussionmentioning
confidence: 79%
“…The steam explosion of raw hemp technical fibers (RF) was performed according to a previously described method after a basic impregnation (NaOH, 8% w/w). The optimal parameters of our previous study (190°C, 4 min) were used to produced exploded fibers (EF) composed of ~ 90% of elementary fibers (Sauvageon et al, 2018). Bleaching treatments were performed starting from raw and exploded fibers (producing respectively BRF and BEF).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous paper, we described the optimization of fine hemp fibers extraction using SE [4]. This method allowed an efficient degumming of the technical hemp fibers and the production of a cotton-like material.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of SE on biomass combines a chemical hydrolysis, a thermal effect during the steam treatment and a mechanical effect during the explosive decompression. SE induces (1) a partial breakdown of glucosidic and lignin-hemicelluloses linkages by hydrolysis and of intramolecular hydrogen bonds (2) a thermo-mechanical defibration due to the flash evaporation of water in the cell wall (Jacquet et al, 2015, Sauvageon et al, 2018. As a result, SE is described as an efficient way to decrease the particle size and to induce an extensive defibration of the biomass.…”
Section: Introductionmentioning
confidence: 99%